Software and computing for Run 3 of the ATLAS experiment at the LHC - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; Sauer, Christof; et al. (The European physical journal. C, Particles and fields, 2025)
The ATLAS experiment has developed extensive software and distributed computing systems for Run 3 of the LHC. These systems are described in detail, including software infrastructure and workflows, distributed data and workload management, database infrastructure, and validation. The use of these systems to prepare the data for physics analysis and assess its quality are described, along with the software tools used for data analysis itself. An outlook for the development of these projects towards Run 4 is also provided.
Online veröffentlicht: 06. März 2025
*ATLAS Collaboration: G. Aad, A. Ackermann, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrychyan, D.F. Rassloff, L. Sanfilippo, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Gesehen am 23.02.2026